EFFECTS OF SPORTS AND GAMES ON SECONDARY SCHOOLS STUDENTS’ACADEMIC PERFORMANCE IN MOROGORO URBAN DISTRICT, TANZANIA - Benedicto Kazuzuru,; George F. Ibrahim, (IJRDO- Journal of Educational Research, 2020)
This study was conducted to determine whether participating in sports and games has effect on students’ academic achievement in Morogoro urban district secondary schools. It also investigated challenges facing students who participate in sports and games as well as students’ opinions on the roles of sports and games in academic performance. A structured questionnaire was used to collect data from 120 students. One-way analysis of variance (ANOVA) was used to compare academic performance between non players, minimum players, regular players and frequent players. Descriptive statistic (frequencies and percentages) were used to assess students’ challenges on sports and games as well as their opinions on role of sports and games on academic performance. The results reveal that there is no statistically significant difference between non players, minimum players, regular and frequent players (F = 0.60, p = 0.66). Study also found that lack of facilities, including playing grounds to be the main challenge facing students in sports and games. As regard to students’ opinions on roles of games and sports in academic performance, the result found that majority of the students had inconclusive opinions, even though most had positive opinions on the existence of sports and games in schools. It is recommended to the stakeholders (parents, schools, government) to promote sports and games by addressing the raised challenges.